THE NOTIONS OF UNITY AND MULTITUDE IN SOCIAL MOVEMENTS. REFLECTIONS ON TWO LATIN-AMERICAN’ CASES (Andamios, Revista de Investigación Social, 2011)
This article is about social movements’ unity and articulation, and the problems that emerge when this goal is pursued. In our analysis we use the notions of “unity” and “multitude”, as they have conceptualized in the field of political philosophy. Our central question is: Which are the concepts from the field of political philosophy that better account for the dynamics embraced by the movements? We explore the case of the Asambleas Barriales (Neighborhood Assemblies) that emerged in Argentina in December 2001 in the context of a deep economic and political crisis, and the case of the Promotora de la Unidad Nacional contra el Neoliberalismo (Promotora for National Unity against Neo-liberalism) created at the end of 2002 in Mexico with the intention to keep the policies implemented by the Fox administration under watch. The article is organized in three sections. In the first section we propose some conceptualizations around the notions of unity and multitu-de considering three particular dimensions. In the second section we explore and analyze the cases. In the final section we conclude.
Keywords: Social movements; unity; multitude; neighborhood assemblies and promotora for national unity against neoliberalism